Options for reducing greenhouse gas emissions from agriculture and food systems - Vos, Rob; Martin, Will (International Food Policy Research Institute, 2025)
Food systems generate about one third of global greenhouse gas (GHG) emissions. Without reducing them, it will not be possible to stabilize the climate and keep the increase in global temperature below 1.5 oC from pre-industrial levels. About 50 percent of agricultural emissions (in CO2eq) come from methane, a super potent GHG, mostly from livestock production and rice cultivation. We consider six broad potential approaches to reducing emissions from agriculture—emission taxes; repurposing of farm support; regulations and conditionality; investing in green innovations; emission reduction credits, and demand-side interventions. We find that carbon taxes on most agricultural production emissions are likely much less effective than for emissions from combustion. Simple rearrangement or reduction of agricultural support will have only small impacts in terms of improving human and planetary health. By contrast, repurposing agricultural support towards R&D on sustainable agricultural intensification could generate major efficiency gains, sharply reduce emissions and improve food security. Regulatory approaches, including conditionality and payment for environmental services (PES) can be counterproductive if they lower yields and require expansion of agricultural land use. The potential benefits of emission reduction credits are greatly diminished by challenges in defining their baselines. Demand interventions designed to contribute both to environmental goals and improvements in health outcomes may also play a supporting role. Since multiple sustainable development goals are to be achieved, no single instrument by itself will be effective. Instead, multiple policy instruments will need to be bundled and targeted to create synergies and address trade-offs.